CONTROLE DA MATOCOMPETIÇÃO EM PLANTIOS DE DOIS CLONES DE Eucalyptus × urograndis NO AMAPÁ - Perseu da Silva Aparício (Ciência Florestal, 2010)
This study aimed to analyze the initial growth of two clones of the hybrid Eucalyptus × urograndis in different weed management systems, during the year of implantation, in the Amapá area. The study was developed in Amapá Florestal Celulose S.A. (AMCEL), from September/2006 until November/2007, with two experimental areas located in Itaubal, AP (0°42¿N; 50°450°48¿W). Two clones of the hybrid Eucalyptus × urograndis (H3911 and H3243) were planted by mechanized form, with one clone per stand. The areas were cleaned using an application of glyphosate. A repeated measure model was used. Treatments consisted of the two clones and six silvicultural treatments with four replicates (T1: without cleaning; T2: total cleaning; T3: cleaning in two bands of 50cm at the plantation line; T4: cleaning in two bands of 75cm at the plantation line; T5: cleaning in two bands of 100cm at the plantation line; and T6: circle cleaning with 75cm of ray). In the beginning of the evaluation, only plants height were measured. From the fifth month on, the diameter, at 1.30m (DBH), was also measured. The Mauchly sphericity test was carried out and hypotheses of nullity were tested for interactions time x clone and time x clone x types of cleanness. Differences among means were compared by Tukey test (p < 0.05). For clone H3911, the treatment T5 and Total Cleaning showed statistically similar heights, which did not occur with the other treatments. For the DBH of clone H3911 plants, growth was similar, though with different rates of growth during the evaluation period, where T1 and T6 showed greater sensitivity to competition. The heights of clone H3243 plants remained statistically similar at the end of the experiment, however, for DAP, it was observed that plants from T1 were more sensitive to the presence and effect of weeds, athough they had a mean DBH statistically superior to other treatments in the first month of evaluation.The growth of plants from the Total Cleaning treatment was superior in comparison to the other treatments over a year of assessment for both clones tested.